Low grade mucoepidermoid carcinoma in a setting of Warthin's tumor - Manisha Mohapatra; S Satyanarayana (Wolters Kluwer Medknow Publications, 2012)
Warthin's tumor also known as papillary cystadenoma lymphomatosum is a common benign salivary gland neoplasm that occurs exclusively in parotid gland. Rarely, the tumor can undergo carcinomatous or lymphomatous transformation of epithelial or lymphoid component, respectively. Herein, we describe a case of 55-year-old female who had undergone parotidectomy for a rapidly growing tumor in the right parotid gland. The case was diagnosed as mucoepidermoid carcinoma developed in a setting of Warthin's tumor based on the histomorphology, special staining characters, and immunohistochemical findings. The pathogenesis and differential diagnoses of such rare malignancy has been discussed briefly.